Top-down fabrication of single crystal silicon nanoparticles
Patent Information
- Application Number
- KR1020230051962
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-04-20
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-04-20
Smart Images

Figure 112023044617078-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing downward-flow single-crystal silicon nanoparticles, and specifically, to a method for manufacturing silicon nanoparticles that enables mass production of silicon nanoparticles having a uniform particle size distribution by facilitating easy control of particle size. Background Technology
[0002] As the demand for alternative energy increases due to environmental pollution and the depletion of fossil fuels, there is also a demand for improved performance of secondary batteries. Specifically, there is a growing need for high-energy-density lithium-ion batteries to power high-performance electronic devices and extend the driving range of electric vehicles. Accordingly, silicon, with a capacity of approximately 4,200 mAh / g—more than 10 times greater than graphite (approximately 372 mAh / g)—is attracting attention as a next-generation anode material for lithium-ion batteries. However, lithium-ion batteries using silicon as an anode material face a problem where the volume of silicon expands by more than 300% during charging and discharging, causing cracks to form on the surface and within. Therefore, silicon nanoparticles, which exhibit minimal volume change during charging and discharging, have been proposed as an anode material.
[0003] Conventional methods for manufacturing silicon nanoparticles include bottom-up methods such as the thermal decomposition of trisilane or Chemical Vapor Deposition using disilane as a precursor. While bottom-up methods can produce silicon particles of various sizes ranging from nanometers to micrometers, they have disadvantages such as low purity, the presence of internal defects, and large variation in particle size. Alternatively, silicon nanoparticles can be manufactured using top-down methods that break down large particles into smaller ones, such as irradiating a silicon substrate with a laser or grinding silicon lumps with a grinder. Although the standard deviation of silicon nanoparticle size produced by these methods is smaller than that of bottom-up methods, the produced nanoparticles are not perfectly spherical, and the particle sizes that can be manufactured are limited.
[0004] Therefore, there is a need for research on methods to manufacture highly spherical silicon nanoparticles with a uniform particle size distribution that are capable of mass production. The problem to be solved
[0005] The objective of the present invention is to solve the problems of the prior art described above by providing a method for manufacturing single-crystal silicon nanoparticles that can easily control particle size and enable mass production. means of solving the problem
[0006] A method for manufacturing silicon nanoparticles according to the present invention comprises: a step of annealing a silicon substrate having one or more pillar structures; a step of oxidizing the annealed silicon substrate to form silicon nanoparticles having an oxide film on the surface; and a step of removing the oxide film on the surface of the silicon nanoparticles.
[0007] In the method for manufacturing silicon nanoparticles according to the present invention, the aspect ratio of the pillar structure may be 2 to 5.
[0008] In the method for manufacturing silicon nanoparticles according to the present invention, the silicon nanoparticles may have a monodisperse particle size distribution.
[0009] In the method for manufacturing silicon nanoparticles according to the present invention, the average particle size (D50) of the silicon nanoparticles may be 1 to 200 nm.
[0010] In the method for manufacturing silicon nanoparticles according to the present invention, the particle size distribution width ((D90-D10) / D50) of the silicon nanoparticles may be 1.0 or less.
[0011] In the method for manufacturing silicon nanoparticles according to the present invention, the thickness of the oxide film may be 1 to 1000 nm.
[0012] In the method for manufacturing silicon nanoparticles according to the present invention, the average particle size of the silicon nanoparticles can be controlled according to the oxidation time of the annealed silicon substrate.
[0013] In the method for manufacturing silicon nanoparticles according to the present invention, the oxidation time of the annealed silicon substrate may be 10 to 120 minutes.
[0014] In the method for manufacturing silicon nanoparticles according to the present invention, the annealing temperature may be 500 to 1400 ℃.
[0015] In the method for manufacturing silicon nanoparticles according to the present invention, the step of removing the oxide film can be performed by immersing the silicon nanoparticles having an oxide film on their surface in an etching solution to remove it.
[0016] In the method for manufacturing silicon nanoparticles according to the present invention, the circularity of the silicon nanoparticles may be 0.9 or higher.
[0017] In the method for manufacturing silicon nanoparticles according to the present invention, the silicon nanoparticles may have a nanorod shape.
[0018] In the method for manufacturing silicon nanoparticles according to the present invention, the silicon nanoparticles may have single crystallinity.
[0019] The present invention includes silicon nanoparticles produced by the method for producing silicon nanoparticles described above.
[0020] The monodisperse single-crystal silicon nanoparticle powder according to the present invention has a circularity of 0.9 or higher and a particle size distribution width of 0.3 or lower.
[0021] The monodisperse single-crystal silicon nanoparticle powder according to the present invention has a particle size distribution width of 0.3 or less and has a nanorod shape.
[0022] The negative electrode material for a lithium secondary battery according to the present invention comprises the monodisperse single-crystal silicon nanoparticle powder described above. Effects of the invention
[0023] The method for manufacturing downward single-crystal silicon nanoparticles according to the present invention can easily control the size of the silicon nanoparticles.
[0024] In addition, the present invention provides a method for manufacturing single-crystal silicon nanoparticles having a uniform particle size distribution.
[0025] Furthermore, silicon nanoparticles with high sphericity can be manufactured. Brief explanation of the drawing
[0026] FIG. 1 is a diagram illustrating a method for manufacturing silicon nanoparticles according to one embodiment. FIG. 2 is a drawing illustrating a silicon substrate annealed by a method according to one embodiment. FIG. 3 is a diagram illustrating silicon nanoparticles having a surface oxide film prepared by a method according to one embodiment. FIG. 4 is a scanning electron microscope (SEM) image of a silicon substrate before and after annealing according to one embodiment. Figure 5 is an SEM image observing a cross-section of silicon nanoparticles having a surface oxide film according to one embodiment, and a graph measuring the thickness of the oxide film according to the oxidation time of the silicon nanoparticles. Figure 6 is a graph showing the shortening length of silicon nanoparticles according to the oxidation time of a silicon substrate in one embodiment. FIG. 7 is a graph measuring the ratio of the short axis to the long axis of silicon nanoparticles according to the aspect ratio of a silicon substrate according to one embodiment. FIG. 8 is an SEM image (a) and an AFM image (b) of silicon nanoparticles according to one embodiment. Specific details for implementing the invention
[0027] The method for manufacturing silicon nanoparticles according to the present invention is described in detail. The terms used in this specification have been selected to be as widely used as possible in consideration of the functions of the present invention; however, these terms may vary depending on the intent of those skilled in the relevant field, case law, the emergence of new technologies, etc. Unless otherwise defined, technical and scientific terms used may have the meaning commonly understood by those skilled in the art to which this invention pertains.
[0028] In this specification and the appended claims, terms such as “comprising” or “having” mean that the features or components described in the specification exist, and unless specifically limited, do not preclude the possibility that one or more other features or components may be added.
[0029] In this specification and the appended claims, terms such as "first," "second," etc. are used not in a limiting sense, but for the purpose of distinguishing one component from another.
[0030] Singular expressions used in this specification and the appended claims include plural expressions unless the context clearly indicates that they are singular. Additionally, plural expressions include singular expressions unless the context clearly indicates that they are plural.
[0031] Additionally, the numerical ranges used in this specification include lower and upper limits and all values within the range, increments logically derived from the form and width of the defined range, all of which are limited values, and all possible combinations of upper and lower limits of numerical ranges defined in different forms. Unless otherwise specifically defined in this specification, values outside the numerical range that may occur due to experimental error or rounding are also included in the defined numerical range.
[0032] Terms such as “approximately” used in this specification and the appended claims are used to encompass tolerances when tolerances exist.
[0033] A method for manufacturing silicon nanoparticles according to the present invention comprises: a step of annealing a silicon substrate having one or more pillar structures; a step of oxidizing the annealed silicon substrate to form silicon nanoparticles having an oxide film on the surface; and a step of removing the oxide film on the surface of the silicon nanoparticles.
[0034] A silicon substrate comprising one or more pillar structures may have one or more silicon pillar structures, preferably two or more, formed on a silicon flat plate, wherein a plurality of silicon pillars are formed on a silicon flat plate.
[0035] When a silicon substrate containing a pillar structure is annealed at high temperature, the structure of the silicon substrate may change due to Rayleigh-Plateau instability as diffusion occurs on the surface of the silicon substrate.
[0036] Rayleigh-Plato instability refers to a phenomenon in which a descending fluid flow separates into shapes with equal volume but smaller surface area to minimize surface energy. When a silicon substrate containing a pillar structure is annealed at high temperatures, the solid silicon substrate behaves similarly to a fluid, which can lead to Rayleigh-Plato instability. Consequently, during high-temperature annealing, the pillar structure of the silicon substrate diffuses in a direction that minimizes surface energy, causing a change in shape. This results in the formation of regions with larger and smaller diameters along the plane of the substrate; due to Rayleigh-Plato instability, the smaller-diameter regions become even smaller, ultimately allowing the pillar structure to easily separate from the substrate to obtain silicon nanoparticles. The Rayleigh-Plato instability of the silicon pillar structure described above is significantly influenced by the aspect ratio (pillar length / pillar diameter), and silicon nanoparticles of various shapes can be produced depending on the value of the aspect ratio.
[0037] In one embodiment, the column structure can be transformed into a balloon structure by annealing, so that the diameter of the upper part is larger than the diameter of the lower part.
[0038] The structure of the annealed silicon substrate may change depending on the aspect ratio of the pillar structure prior to annealing. Specifically, the aspect ratio of the pillar structure may be 1 to 9 or 2 to 7, and preferably 2 to 5. In one embodiment, when the aspect ratio of the pillar structure is 3 or less, it may have a spherical balloon structure, and when the aspect ratio of the pillar structure is 4 to 5, when the silicon substrate is annealed, the length of the upper part of the pillar structure increases, and an elliptical balloon structure may be exhibited. The diameter of the pillar structure may be 0.5 to 2.0 μm, 0.6 to 1.9 μm, or 0.7 to 1.8 μm, and preferably 0.8 to 1.6 μm. Alternatively, it may be 0.5 µm or more, 0.6 µm or more, 0.7 µm or more, 0.8 µm or more, or 0.9 µm or more, and as an upper limit, it may be 2.0 µm or more, 1.9 µm or more, 1.8 µm or more, 1.7 µm or more, or 1.6 µm or more.
[0039] Since the pillar structure has a diameter within the range described above, when the diameter of the lower portion of the silicon substrate including the pillar structure is reduced by annealing, the lower portion of the pillar structure may not be separated from the substrate.
[0040] The annealing temperature may be 500 to 1400°C or 700 to 1200°C, preferably 900 to 1180°C. Alternatively, it may be 500°C or higher, 700°C or higher, 900°C or higher, or 1100°C or higher, and the upper limit may be 1400°C or lower, 1300°C or lower, 1200°C or lower, or 1150°C or lower. When annealing is performed within the above-described temperature range, the solid silicon substrate exhibits fluid-like behavior, and the structure of the silicon substrate can easily change from a pillar structure to a balloon structure due to Rayleigh-Plato instability.
[0041] In one embodiment, silicon nanoparticles having an oxide film on the surface of a silicon substrate can be produced by oxidizing an annealed silicon substrate.
[0042] The average particle size of silicon nanoparticles produced can be controlled by controlling the oxidation time of an annealed silicon substrate. When an annealed silicon substrate is oxidized, the silicon on the substrate is consumed, and the surface of the silicon substrate is oxidized at a uniform rate, thereby forming a surface oxide film. Therefore, as the oxidation time increases, the amount of silicon in the balloon structure located on the substrate consumed increases, and thus the particle size of the silicon nanoparticles produced can be reduced. Specifically, the oxidation time may be 10 to 120 minutes, 15 to 100 minutes, 20 to 90 minutes, or 25 to 80 minutes, or 10 minutes or more, 20 minutes or more, 25 minutes or more, or 30 minutes or more, and as an upper limit, 120 minutes or less, 100 minutes or less, or 80 minutes or less.
[0043] In one embodiment, the thickness of the oxide film can be controlled by adjusting the oxidation time. As the oxidation time increases, the silicon in the balloon structure surrounded by the oxide film is oxidized and consumed, and as the thickness of the oxide film increases, the particle size of the silicon nanoparticles can decrease.
[0044] The oxide film can be formed on a silicon substrate with a uniform thickness, and the thickness of the oxide film can be 1 to 1000 nm, 20 to 800 nm, or 40 to 600 nm, preferably 100 to 500 nm. Alternatively, it can be 1 nm or more, 5 nm or more, 10 nm or more, 30 nm or more, 50 nm or more, or 100 nm or more, and as an upper limit, it can be 1000 nm or less, 800 nm or less, 600 nm or less, 400 nm or less, or 200 nm or less.
[0045] By controlling the oxidation time, the particle size of silicon nanoparticles can be precisely controlled to easily produce silicon nanoparticles of a desired particle size, and silicon nanoparticles with a uniform particle size distribution can be produced.
[0046] During the oxidation of a balloon-structured silicon substrate, the entire surface of the silicon substrate is surrounded by an oxide film, and the narrow lower part of the balloon structure is separated from the silicon substrate, thereby enabling the production of silicon nanoparticles having a surface oxide film.
[0047] There are no restrictions on the method of oxidation, and any known method may be used. For example, it may be manufactured by a wet oxidation method in which the oxidizing agent contains water, or by a dry oxidation method using oxygen gas as the oxidizing agent, but it is preferable to use a dry oxidation method to form an oxide film of uniform thickness on the surface of a silicon substrate containing a balloon structure.
[0048] After the step of forming silicon nanoparticles having the above-mentioned surface oxide film, silicon nanoparticles can be manufactured by removing the oxide film on the surface of the silicon nanoparticles. The silicon nanoparticles can be manufactured in a spherical or nanorod shape depending on the aspect ratio of the pillar structure contained in the silicon substrate, and it is advantageous to simply manufacture silicon nanoparticles of a desired shape and size by controlling the particle size of the silicon nanoparticles according to the oxidation time of the annealed silicon substrate.
[0049] In one embodiment, the surface oxide film of silicon nanoparticles can be removed by immersing them in an etching solution. Specifically, the etching solution may be a diluted hydrofluoric acid solution (DHF) in which hydrofluoric acid (HF) and deionized water are mixed in a mass ratio of 1:1 to 100, 1:5 to 50, or 1:8 to 30. Alternatively, the oxide film may be etched using a buffered oxide etchant (BOE) in which hydrofluoric acid (HF) and ammonium fluoride (NH4F) are mixed in a mass ratio of 1:3 to 50, 1:5 to 30, or 1:6 to 10, but the present invention is not limited by the specific material of the etching solution and the method for removing the oxide film.
[0050] The present invention includes silicon nanoparticles manufactured by the method described above.
[0051] In the case of conventional silicon particles, during the charge and discharge cycles of a battery, each atom reacts with up to four or more lithium atoms, and during this process, rapid volume expansion of approximately 400% can occur. Due to this volume expansion, cracks may form in the electrode, leading to its destruction and separation of the active material and the current collector. Furthermore, at the sites where cracks occur, the reaction between the electrolyte additive and lithium ions can form a solid film such as a Solid Electrolyte Interphase (SEI) layer, which can lead to problems such as increased internal resistance and capacity loss, thereby degrading the battery's characteristics. Therefore, by reducing the diameter of the silicon particles to the nanometer level, volume expansion caused by charge and discharge can be significantly reduced.
[0052] In one embodiment, the average particle size (D50) of the silicon nanoparticles may be 1 to 200 nm or 50 to 160 nm, and advantageously 100 to 130 nm. Alternatively, it may be 1 nm or more, 10 nm or more, 30 nm or more, 50 nm or more, or 100 nm or more, and the upper limit may be 200 nm or less, 170 nm or less, or 130 nm or less. Silicon nanoparticles having a particle size within the above-described range are advantageous because the small particle size can significantly reduce the occurrence of cracks due to volume expansion.
[0053] In one embodiment, the particle size distribution width of the silicon nanoparticles may be 1.0 or less, 0.7 or less, 0.5 or less, 0.3 or less, or 0.1 or less, and advantageously, the particle size may have uniform monodispersity.
[0054] The particle size distribution width can be expressed by the following Equation 1.
[0055] [Equation 1]
[0056] Particle size distribution width = (D90-D10) / D50
[0057] D90, D50, and D10 represent the particle sizes at which the cumulative percentages of the total silicon nanoparticle size distribution reach 90%, 50%, and 10%, respectively. A narrower particle size distribution width indicates that the silicon nanoparticles can have a monodisperse particle size distribution with a small variation in particle size. Since silicon nanoparticles with an average particle size within the aforementioned range exhibit monodispersity, when used as a negative electrode material for a lithium secondary battery, the volume change is small during charge and discharge cycles, and high capacity can be maintained. Furthermore, since the manufactured silicon nanoparticles possess single crystallinity, it is advantageous for improving the electrochemical performance of the secondary battery.
[0058] In one embodiment, the shape of the silicon nanoparticles may be spherical or nanorod-shaped. As described above, when manufacturing silicon nanoparticles, the shape of the silicon nanoparticles can be controlled by changing the aspect ratio of the pillar structure of the substrate.
[0059] In one embodiment, when the silicon nanoparticles have a spherical shape, the circularity of the silicon nanoparticles may be 0.9 or higher, 0.93 or higher, 0.96 or higher, or 0.99 or higher, and advantageously, the circularity may be 1.0. Circularity is a numerical value indicating the degree to which the shape of an object is close to a sphere, and can be expressed by the following Equation 2.
[0060] [Equation 2]
[0061] Sphericity = A s / A p
[0062] A p represents the surface area of the silicon nanoparticle, and A s represents the surface area of a sphere having the same volume as the above silicon nanoparticle. In other words, the closer the sphericity is to 1, the more similar the particle is to a sphere. When silicon nanoparticle powder containing multiple silicon nanoparticles with high sphericity is used as a negative electrode material for a lithium-ion battery, the electrode density can be increased and the volume expansion rate can be reduced. It is possible to manufacture a lithium secondary battery in which not only is the capacity improved by increasing the electrode density, but the occurrence of cracks is significantly reduced by decreasing the volume expansion rate of the electrode.
[0063] In another aspect of the present invention, silicon nanoparticles may have a nanorod shape. Although not necessarily limited to this interpretation, when silicon nanoparticle powder containing a plurality of monodisperse single-crystalline silicon nanoparticles with a nanorod shape is used as a negative electrode material for a lithium-ion battery, it is advantageous to have a high specific surface area, shorten the diffusion distance of lithium ions to enable rapid solid-state diffusion, and reduce internal stress of the particles due to volume change during charging and discharging, thereby providing the effect of increasing the capacity of the battery.
[0064] The present invention will be explained in more detail below through examples.
[0065] (Example 1)
[0066] A silicon substrate containing a pillar structure with an aspect ratio of 3 and a particle size of 1.6 μm was annealed at 1150°C for 60 minutes. The annealed silicon substrate was reacted with oxygen gas in a reaction chamber for about 25 minutes to form silicon nanoparticles having an oxide film on the surface of the silicon substrate. Subsequently, silicon nanoparticles containing the oxide film were immersed in a diluted hydrofluoric acid solution (DHF) prepared by mixing hydrofluoric acid (HF) and deionized water in a ratio of 1:10 to remove the oxide film on the surface, thereby producing silicon nanoparticles.
[0067] (Example 2)
[0068] Silicon nanoparticles were prepared in the same manner as in Example 1, except that a silicon substrate with a pillar structure aspect ratio of 5 was used.
[0069] (Example 3)
[0070] Silicon nanoparticles were prepared in the same manner as in Example 1, except that the oxidation of the annealed silicon substrate was performed for about 70 minutes.
[0071] (Example 4)
[0072] Silicon nanoparticles were prepared in the same manner as in Example 1, except that the oxidation of the annealed silicon substrate was performed for about 120 minutes.
[0073] (Example 5)
[0074] Silicon nanoparticles were prepared in the same manner as in Example 1, except that the oxidation of the annealed silicon substrate was performed for about 170 minutes.
[0075] (Example 6)
[0076] Silicon nanoparticles were prepared in the same manner as in Example 1, except that a silicon substrate with a columnar structure aspect ratio of 4.5 was used.
[0077] (Example 7)
[0078] Silicon nanoparticles were prepared in the same manner as in Example 1, except that a silicon substrate with a columnar structure aspect ratio of 2 was used.
[0079] FIG. 1 is a diagram illustrating a method for manufacturing silicon nanoparticles according to Example 1. When a silicon substrate containing a pillar structure is annealed, the pillar structure changes into a balloon structure, and when the annealed silicon substrate is oxidized, an oxide film of uniform thickness is formed on the surface of the balloon structure. As the oxidation time increases, the lower end with a smaller diameter separates from the substrate, thereby producing silicon nanoparticles having a surface oxide film. Subsequently, the silicon nanoparticles are etched to remove the oxide film on the surface of the silicon nanoparticles, thereby obtaining silicon nanoparticles.
[0080] FIG. 2 is a diagram illustrating the shape of an annealed silicon substrate when silicon nanoparticles are prepared by the methods of Example 1 and Example 2. In the case of Example 1, when annealing a silicon substrate containing a pillar structure with an aspect ratio of 3, a spherical balloon structure was formed, and when annealing a silicon substrate with a pillar structure having an aspect ratio of 5 as in Example 2, an elliptical balloon structure was formed. The shape of the silicon nanoparticles prepared can be changed by adjusting the aspect ratio.
[0081] Figure 3 is a diagram showing the change in particle size of silicon nanoparticles according to oxidation time when silicon nanoparticles are prepared by the method of Example 1. When the oxidation time is short, the amount of silicon consumed from the substrate is small, so the particle size of the silicon nanoparticles produced is large, but as the oxidation time increases, the amount of silicon nanoparticles consumed also increases, the thickness of the oxide film becomes thicker, and the particle size of the silicon nanoparticles produced decreases.
[0082] Figure 4 is a scanning electron microscope (SEM) image of a silicon substrate containing a pillar structure before and after annealing when manufacturing silicon nanoparticles by the method of Example 1. The silicon substrate containing a pillar structure of Example 1 changed from a pillar structure to a balloon structure through annealing. When the pillar-structured silicon is heat-treated at a high temperature, the solid-state silicon exhibits behavior similar to a fluid; consequently, due to Rayleigh-Plato instability, the pillar-structured silicon particles formed a balloon structure to reduce their surface area. As the pillar-structured silicon substrate formed a balloon structure with different widths at the top and bottom, the silicon substrate was oxidized, and the narrower region was separated into individual silicon nanoparticles through oxidation, making it easy to mass-produce silicon nanoparticles.
[0083] Figure 5 shows a scanning electron microscope (SEM) image (a) of a cross-section of silicon nanoparticles having a surface oxide film prepared by the method of Example 1, and a graph (b) measuring the thickness of the surface oxide film according to oxidation time. Figure 5(a) shows a cross-section of silicon nanoparticles having a surface oxide film prepared by Focused Ion Beam Milling (FIB) and observed using a scanning electron microscope. As the balloon-shaped silicon substrate is consumed, an oxide film can be formed on the surface of the balloon-shaped silicon, and it can be confirmed that the silicon nanoparticles are separated from the substrate as the narrow lower portion is consumed by oxidation. Furthermore, as shown in Figure 5(b), the oxide film thickness of Example 1, with an oxidation time of 25 minutes, was 0.5 μm or less, whereas in the case of Example 4, with an increased oxidation time of 120 minutes, the oxide film thickness showed a significantly increased trend to approximately 0.9 μm.
[0084] More specifically, FIG. 6 is a graph showing the measured short-axis lengths of multiple silicon nanoparticles prepared by the methods according to Examples 1, 3, and 4. The average short-axis length of the silicon nanoparticles prepared by the method of Example 1 was approximately 460 nm, the average short-axis length of the silicon nanoparticles prepared by the method of Example 3 was approximately 215 nm, and the average short-axis length of the silicon nanoparticles prepared by the method of Example 4 was measured to be approximately 69 nm. When silicon nanoparticles were prepared using a columnar silicon substrate having the same aspect ratio, the short-axis length decreased as the oxidation time increased. During the preparation of silicon nanoparticles, as an oxide film is formed on the surface while consuming the balloon-shaped silicon, the consumption of silicon nanoparticles located inside the oxide film increased as the oxidation time lengthened. Therefore, the silicon nanoparticles of Example 4, which had a long oxidation time, were measured to have the smallest particle size. Thus, the particle size of the silicon nanoparticles prepared can be easily controlled by controlling the oxidation process time.
[0085] Figure 7 is a graph measuring the ratio of the major axis to the minor axis of silicon nanoparticles prepared by the methods of Example 1 and Example 6. The ratio of the major axis to the minor axis length is D T / D L It was indicated as, and D T represents the major axis length of the silicon nanoparticle, and D L represents the minor axis length of the silicon nanoparticle. For multiple silicon nanoparticles prepared from a silicon substrate containing multiple pillar structures, the ratio of the major axis to the minor axis length of each silicon nanoparticle was measured, and the number of silicon nanoparticles having said ratio was measured and plotted on a graph. As shown in Fig. 7, it can be confirmed that the silicon nanoparticles prepared by the methods of Examples 1 and 6 have a narrow particle size distribution width and are nanoparticles with a relatively uniform size. Specifically, the silicon nanoparticle of Example 1 prepared from a silicon substrate containing a pillar structure with an aspect ratio of 3 is D T / D L While the average is approximately 2.25, in the case of Example 6 using a silicon substrate containing a pillar structure with an aspect ratio of 4.5, D of the silicon nanoparticles T / D L The average was approximately 3.58, and the length of the major axis increased compared to Example 1. By controlling the aspect ratio of the pillar structure included in the initial silicon substrate, not only can the shape of the silicon nanoparticles being manufactured be controlled, but silicon nanoparticles with a uniform particle size distribution can also be manufactured.
[0086] Figure 8 shows an SEM image (a) and an AFM image (b) of silicon nanoparticles prepared by the method according to Example 1. When silicon nanoparticles containing a surface oxide film are immersed in an etching solution, the surface oxide film is removed, and silicon nanoparticles can be obtained. As shown in Figure 8, nanorod-shaped silicon nanoparticles were prepared, and it can be confirmed that not only were high-quality silicon nanoparticles without defects such as cracks prepared, but also monodisperse silicon nanoparticles of uniform size were prepared.
[0087] As described above, the present invention has been explained by specific details, limited embodiments, and drawings; however, this is provided merely to aid in a more comprehensive understanding of the invention, and the invention is not limited to the above embodiments. Those skilled in the art can make various modifications and variations from this description.
[0088] Accordingly, the scope of the present invention is not limited to the described embodiments, and all things equivalent to or having equivalent variations to the claims set forth below, as well as the claims set forth below, shall be considered to fall within the scope of the concept of the present invention.
Claims
Claim 1 A method for manufacturing silicon nanoparticles comprising: a step of annealing a silicon substrate having one or more pillar structures; a step of oxidizing the annealed silicon substrate to form silicon nanoparticles having an oxide film on their surface; and a step of removing the oxide film on the surface of the silicon nanoparticles having an oxide film on their surface; wherein the silicon nanoparticles have a spherical or nanorod shape, the silicon nanoparticles have a monodisperse particle size distribution, the silicon nanoparticles have an average particle size of 100 to 130 nm, and the silicon nanoparticles have a particle size distribution width ((D90-D10) / D50) of 1.0 or less. Claim 2 A method for manufacturing silicon nanoparticles according to claim 1, wherein the aspect ratio of the pillar structure is 2 to 5. Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 A method for manufacturing silicon nanoparticles according to claim 1, wherein the thickness of the oxide film is 1 to 1000 nm. Claim 7 A method for manufacturing silicon nanoparticles according to claim 1, wherein the average particle size of the silicon nanoparticles is controlled according to the oxidation time of the annealed silicon substrate. Claim 8 A method for manufacturing silicon nanoparticles according to claim 7, wherein the oxidation time of the annealed silicon substrate is 10 to 120 minutes. Claim 9 A method for manufacturing silicon nanoparticles according to claim 1, wherein the annealing temperature is 500 to 1400℃. Claim 10 A method for manufacturing silicon nanoparticles according to claim 1, wherein the step of removing the oxide film is to remove the oxide film by immersing the silicon nanoparticles having the oxide film on their surface in an etching solution. Claim 11 A method for manufacturing silicon nanoparticles according to claim 1, wherein, when the silicon nanoparticles are spherical in shape, the circularity is 0.9 or higher. Claim 12 delete Claim 13 A method for manufacturing silicon nanoparticles according to claim 1, wherein the silicon nanoparticles have single crystallinity. Claim 14 Silicon nanoparticles manufactured by a manufacturing method according to any one of claims 1, 2, 6 to 11 and 13, wherein the silicon nanoparticles have a spherical or nanorod shape, the silicon nanoparticles have a monodisperse particle size distribution, the silicon nanoparticles have an average particle size of 100 to 200 nm, and the silicon nanoparticles have a particle size distribution width ((D90-D10) / D50) of 1.0 or less. Claim 15 delete Claim 16 delete Claim 17 A negative electrode material for a lithium secondary battery comprising silicon nanoparticles of claim 14.
Citation Information
Patent Citations
Nanostructured materials for battery applications
KR102067922B1